2022
DOI: 10.3389/fmed.2022.871861
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Pirfenidone Combined With Immunosuppressant Therapy in Connective Tissue Disease-Associated Interstitial Lung Disease: A 24-Week Prospective Controlled Cohort Study

Abstract: ObjectiveInterstitial lung disease (ILD) is a common manifestation of connective tissue disease (CTD) that manifests as several subtypes with significant differences in prognosis. It is necessary to evaluate the efficacy and safety of pirfenidone (PFD) combined with immunosuppressant (IS) in the treatment of CTD-ILD.MethodsA total of 111 patients with CTD-ILD were enrolled, including those with systemic sclerosis (SSc), inflammatory myopathy (IIM), rheumatoid arthritis (RA), and other CTDs (such as systemic lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…The majority of the studies were rejected because they either included IPF patients (n = 71), had multiple publications for the same study (n = 8), had study designs, comments, or case series (n = 5), or were pharmacokinetic or safety profile studies (n = 4). A final pool of 10 studies was included in the systematic review, with a total of 1990 patients enrolled (Table 1) [9,10,[13][14][15][16][17][18][19][20]. Eight studies reported data on patients treated with pirfenidone, while two studies reported data on patients treated with nintedanib.…”
Section: Summary Of the Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies were rejected because they either included IPF patients (n = 71), had multiple publications for the same study (n = 8), had study designs, comments, or case series (n = 5), or were pharmacokinetic or safety profile studies (n = 4). A final pool of 10 studies was included in the systematic review, with a total of 1990 patients enrolled (Table 1) [9,10,[13][14][15][16][17][18][19][20]. Eight studies reported data on patients treated with pirfenidone, while two studies reported data on patients treated with nintedanib.…”
Section: Summary Of the Main Resultsmentioning
confidence: 99%
“…Eight studies reported data on patients treated with pirfenidone, while two studies reported data on patients treated with nintedanib. Selected papers were published from 2002 to 2022, with a high frequency in the period 2019-2022 (8/10, 80%) [9,10,[13][14][15][16][17][18]. The majority had a randomized, double-blind, placebo-controlled design (8/10, 80%) [9,10,13,[15][16][17]19,20].…”
Section: Summary Of the Main Resultsmentioning
confidence: 99%
“…Both the SENSCIS trial and the ongoing Scleroderma lung study III are assessing the effect of combination therapy with oral anti-fibrotics and MMF. It is therefore likely that future treatment approaches will include a combination of immune modulatory and anti-fibrotic therapy with B cells appearing to play a crucial role in the interaction of these pathways ( 164 , 165 ).…”
Section: Therapeutic Strategies Targeting B Cells In Sscmentioning
confidence: 99%
“…Aside from using immunomodulatory therapies on their own, future directions for combined antifibrotic and immunomodulatory therapies in CTD-ILD will hopefully come from the Scleroderma Lung Study-3 (SLS-3) trial, which will compare the effect of the combination of pirfenidone and mycophenolate with mycophenolate and placebo on FVC at 18 months 55 . There is already promising data for pirfenidone from a recent randomized control trial conducted by Wang et al who demonstrated that patients with SSc-ILD who receive both pirfenidone and immunosuppressants have a statistically significant improvement in FVC at 24 weeks compared to patients receiving only immunosuppressants (56). Furthermore, the LOTUSS study in which patients with SSc-ILD received pirfenidone for either 2 weeks or for 4 weeks demonstrated that pirfenidone has an acceptable side effect and safety profile, so pirfenidone is a promising antifibrotic therapy to continue exploring for patients with CTD-ILD (81).…”
Section: Future Directionsmentioning
confidence: 99%